The weakness examination of wireless network security at the hospital using QoS - Riyanti K.; Sutejo; Ilayaraja M.; Shankar K.; Nguyen P.T.; Hashim W.; Maseleno A. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
Computer networks today are a much needed service. Computer networks enable the shared use of data, software and tools. So that the working group can be communicate more effectively and efficiently. This study aims to determine the existing QoS in Surya Asih Hospital and analyze the deficiencies. (Bahasa: Hospital is Rumah Sakit (RS)) In this research started from collecting data that exist in location either that support hardware or connection internet RS Surya Asih have used Wireless Local Area Network (WLAN) network service. WLAN is a network where can be exchanged data and resources between computers in one building. To know the performance of WLAN network (Wireless Local Area Network In RS Surya Asih, it should be done a measurement analysis of network performance parameters QoS (Quality of Services) is the ability to guarantee the delivery of important data flow Analysis of the performance of WLAN (Wireless Local Area Network) Surya Asih stressed the process of monitoring and measuring network parameters on the network infrastructure such as access speed and transmission capacity, from the point of delivery to the point of receiver that became the demands, the parameters used Bandwidth, Throughput, Delay and Packet Loss. Superior LAN on RS Surya Asih has reliability sufficient maintenance and good network availability Analysis of network performance is seen through Wireshark, Uptime and Downtime results are not bad, The availability of complete devices and fulfilled according to reliability and maintenance is not difficult. QoS parameter test results that bandwidth management shows the use of more bandwidth and evenly distributed to every user of RS Surya Asih Pringsewu network. BEIESP.